2012
DOI: 10.1016/j.bpj.2012.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of mRNA Transport on Stochastic Variability in Protein Levels

Abstract: Homogeneous cell populations can exhibit considerable cell-to-cell variability in protein levels arising from the stochastic nature of the gene-expression process. In particular, transcriptional bursting of mRNAs from the promoter has been implicated as a major source of stochasticity in the expression of many genes. In eukaryotes, transcribed pre-mRNAs have to be exported outside the nucleus and in many cases, export rates can be slow and comparable to mRNA turnover rates. We investigate whether such export p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
146
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(164 citation statements)
references
References 54 publications
8
146
0
Order By: Relevance
“…But whether the selective traffic of proteins and RNAs can act to increase or decrease the stochastic fluctuations in eukaryotic gene expression have only recently been studied. A theoretical study has demonstrated that mRNA transport rate can regulate noise in gene expression (Singh and Bokes, 2012). More recently, Bahar Halpern et al (2015); Battich et al (2015) have shown experimentally that nuclear retention of mRNA in single mammalian cells can reduce noise in mRNA levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…But whether the selective traffic of proteins and RNAs can act to increase or decrease the stochastic fluctuations in eukaryotic gene expression have only recently been studied. A theoretical study has demonstrated that mRNA transport rate can regulate noise in gene expression (Singh and Bokes, 2012). More recently, Bahar Halpern et al (2015); Battich et al (2015) have shown experimentally that nuclear retention of mRNA in single mammalian cells can reduce noise in mRNA levels.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that both negative feedback and compartmentalisation can reduce gene expression noise (Savageau, 1974;Becskei and Serrano, 2000;Simpson et al, 2003;Swain, 2004;Boyer et al, 2005;Tao et al, 2007;Singh and Bokes, 2012;Bahar Halpern et al, 2015;Battich et al, 2015). The central question we sought to address in this paper was: what effect does the combination of both negative feedback and compartmentalisation have on gene expression noise?…”
mentioning
confidence: 99%
“…noise levels are reduced to the Poisson limit. Thus, stochastic delays function to effectively filter out underlying bursty production [64], [65].…”
Section: One-step Conversionmentioning
confidence: 99%
“…Using simulations and transcript counting, it was demonstrated that nuclear retention of mRNA can buffer cytoplasmic noise. While nuclear mRNA content can fluctuate in line with bursty transcription, the delay in the export of transcripts to the cytoplasm produces a constant “trickle” of mRNA from the nucleus, and therefore balances cytoplasmic mRNA levels between bursts (Figure A) …”
Section: Buffering Mechanisms That Reduce the Variability Generated Bmentioning
confidence: 99%